The Role of the Teacher in the Foreign Language Classroom – Past, Recent and Modern Developments - Thomas Tinnefeld (Journal of Linguistics and Language Teaching)
In the present article, the teacher‘s role in the foreign general language and LSP classroom is analysed with respect to the last seventy years as well as modern developments which cover the period from March 2020 to the near future. In retrospect, a glace is cast on the grammar-translation method and the audio-lingual method. The recent developments dealt with cover the communicative approach and the constructivist approach, both of which are still widely used nowadays. The modern developments described refer to the virtual classroom and online teaching. In the article, it is shown that the teacher‘s role in the foreign language classroom from the 1950s to the present day (and certainly further into the future) has changed drastically: whereas up to the late 1970s, the teacher lived a relatively calm and steady life, with his or her role in the classroom being well-defined and stable, his or her role has undergone rapid changes ever since, with the latest developments speeding up this process even more. In accordance with this development, the teacher‘s importance has shown a certain volatility, starting from a relatively high level, then going down and now rising again. Inversely proportional, the complexity of his or her work has constantly increased and will continue doing so. This implies that the teaching profession has become a highly complex, dynamic and future-oriented field of activity.